Implementasi Peraturan Walikota Binjai Nomor 23 Tahun 2019 Tentang Pembentukan Unit Pelaksanaan Teknis Daerah Bus Rapid Transit - Reza Fachrozi; Isnaini Isnaini; Rudi Salam Sinaga (Universitas Medan Area, 2021)
The purpose of this research is to find out and analyze, how the implementation of policies of the Mayor of Binjai in terms of improving the quality and quality of public services, especially transportation services to the people of Binjai City. The method used in this research is descriptive qualitative using the Merille S. Grindle theory where there are several variables that determine the effectiveness of policy implementation. From the results of the study it can be seen that after the implementation of the Mayor's Regulation at the Binjai City Transportation Agency, there was a change where previously the transportation management process, which had been in PD Angkutan Kota Binjai using transportation costs and other transportation, is now transferred to the Transportation Office to manage it with free of charge so that it can make it easier for people to carry out daily activities using Trans Binjai.